EVALUASI KEPUASAN MAHASISWA PENGGUNA OPEN PUBLIC ACCESS CATALOG (OPAC) PERPUSTAKAAN MODERN SULAWESI TENGGARA DENGAN METODE END USER COMPUTING SATISFACTION (EUCS) - Mohammad Ricky Ramadhan Rasyid; Pravasta Guntur Kinantaka (AnoaTIK: Jurnal Teknologi Informasi dan Komputer, 2024)
This study evaluates the satisfaction of student users of the Online Public Access Catalog (OPAC) at the Modern Library of Southeast Sulawesi using the End User Computing Satisfaction (EUCS) method. The research measures five variables: content, accuracy, format, ease of use, and timeliness. A descriptive quantitative method was used in this study with a sample of 81 respondents from a population of 102, selected randomly. Observations were conducted directly by the researcher using a Likert scale questionnaire as the instrument. Data analysis was performed using SPSS version 29. The results showed a very high level of user satisfaction, with scores for each variable exceeding 75%. The conclusion of this study is that student users are satisfied with the implementation of OPAC at the Southeast Sulawesi Modern Library, indicating that the library information system is functioning well.